Prediction of Horizontal Pneumatic Conveying of Large Coal Particles Using Discrete Phase Model - Daolong Yang; Ge Li; Yanxiang Wang; Qingkai Wang; Jianping Li; Qianqian Huang; Youtao Xia; Qian Li (Advances in Materials Science and Engineering)
The pneumatic conveying focusing on gas-solid two-phase flow plays an important role in a conveying system. Previous work has been conducted in the fields of small particles, where the size was less than 5 mm; however, there are few studies regarding large sizes (>5 mm). In order to predict the horizontal pneumatic conveying of large coal particles, the coupling methods based on the Euler–Lagrange approach and discrete phase model (DPM) have been used for the simulated research. Compared with the experimental results under the same working condition, the particle trajectory obtained by simulation is similar to the particle distribution at the same position in the experiment, and it turns out that the simulation method is feasible for the horizontal pneumatic conveying of large particles. Multifactor simulations are also carried out to analyse the effects of particle size, flow field velocity, solid-gas rate, and pipe diameter on the wall abrasion during horizontal pneumatic conveying, which provides simulation reference and design guide for pneumatic conveying of large particles.